Secure e-government web services - Mitrakas, Andreas. (IGI Global (701 E. Chocolate Ave., Hershey, PA, 17033, USA), 2007)
"This book addresses various aspects of building secure E-Government architectures and services; it presents views of experts from academia, policy and the industry to conclude that secure E-Government web services can be deployed in an application-centric, interoperable way. It addresses the narrow yet promising area of web services and sheds new light on this innovative area of applications"--Provided by publisher.